In search of Israeli-Palestinian peace : an urgent call for a new approach to Middle East peace - Har-El, Shai (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2016)
"The fruit of relentless peace activism and many years of philanthropic work in the Middle East Peace Network, In Search of Israeli-Palestinian Peace is Shai Har-El's unique, non-utopian, proactive approach to Middle East peace between Israelis and Palestinians. Recognizing the magnitude, complexity, and gravity of the Israeli-Palestinian conflict and the evidenced limitations of traditional diplomacy, the author offers ideas how to enhance the Middle East peace process by adding a non-governmental peacebuilding component to the peace efforts. Such citizen diplomacy efforts, he argues, should be launched at a preliminary conflict transformation phase leading up to the final conflict resolution phase. The ultimate objective of this preliminary phase is to create--through alternative avenues, such as private diplomacy initiatives, transnational mechanisms, and backchannels--a win-win environment that is conducive to settling the conflict. This book details the concepts, measures, and techniques involved in the process with the understanding that the keystone for peace is the defiant power of the human spirit in both societies that are hungry for peace"--
Includes bibliographical references.
Keywords: Arab-Israeli conflict -- 1993- -- Peace; Palestinian Arabs; Arab-Israeli conflict -- Peace; Palestinian Arabs; Since 1993